2023
DOI: 10.21203/rs.3.rs-2351315/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Accurate aging clocks based on accumulating stochastic variation

Abstract: Aging clocks have provided one of the most significant recent breakthroughs in the biology of aging. Such clocks allow the determination of chronological and increasingly also biological age, which is prerequisite for assessing the effectiveness of interventions in the aging process and preventive treatments of age-related diseases. The most advanced aging clocks are based on age-dependent changes in DNA methylation pattern. The reproducibility of such changes over the life course has reinvigorated the debate … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 50 publications
3
14
0
Order By: Relevance
“…Although recent single‐cell RNAseq questions the existence of such an increase in transcriptional noise with age (Gems & de Magalhães, 2021) others showed that it is sufficient to predict both chronological and biological age. Overall, our data corroborate that gene expression noise occurs especially with chronological age and questions its role in the Smurf transition (Schumacher & Meyer, 2023). Old non‐Smurfs also show some of ATH1 suggesting that inflammation could precede the Smurf transition at least in old individuals although we cannot exclude that at an advanced age, the likelihood of sampling pre‐Smurf or early Smurfs is high and this signal could be due to such individuals contaminating the non‐Smurf samples.…”
Section: Discussionsupporting
confidence: 85%
“…Although recent single‐cell RNAseq questions the existence of such an increase in transcriptional noise with age (Gems & de Magalhães, 2021) others showed that it is sufficient to predict both chronological and biological age. Overall, our data corroborate that gene expression noise occurs especially with chronological age and questions its role in the Smurf transition (Schumacher & Meyer, 2023). Old non‐Smurfs also show some of ATH1 suggesting that inflammation could precede the Smurf transition at least in old individuals although we cannot exclude that at an advanced age, the likelihood of sampling pre‐Smurf or early Smurfs is high and this signal could be due to such individuals contaminating the non‐Smurf samples.…”
Section: Discussionsupporting
confidence: 85%
“…Interestingly, interventions decreasing it were already shown to extend lifespan in nematodes 73 . 75 76 . Old non-Smurfs also show some of ATH1 suggesting that inflammation could precede the Smurf transition at least in old individuals although we cannot exclude that at an advanced age, the likelihood of sampling pre-Smurf or early Smurfs is high and this signal could be due to such individuals contaminating the non-Smurf samples.…”
Section: Discussionmentioning
confidence: 99%
“…To model the evolution of methylation dynamics with time, in a single CpG site, we considered a minimal model of transitions between two states. The proposed model directly relates to the early work of Markov in 1905 and was used for the first time to model the dynamics of methylation in 15 , and more recently in the context of ageing in 16 . In this model cells can be in either an unmethylated or methylated state, U and M respectively, and can transition from one state to the other at rates ν U and ν M (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…To overcome these technical limitations and the lack of biological interpretation, we developed a new model of epigenetic age acceleration based on a mathematical representation of the cellular dynamics of methylation change 15,16 . This model allows mechanistic interpretation of methylation change at CpG sites.…”
Section: Introductionmentioning
confidence: 99%